Diplômes 96. - Pacquement, Alfred; Syring, Marie Luise (Paris : Ecole Nationale Supérieure des Beaux-Arts, 1997)
Adach, Zbigniew ; Angelini, Claire ; Antoine, Guillaume ; Bajevic, Maja ; Bange, Jean-François ; Barmont, Bénédicte ; Beaugeard, Frédéric ; Beaumes, Frédéric ; Benoist-Gironière, Emilie ; Bianciardi, Sandra ; Bibougou, Nathalie ; Blancke, Natalia ; Bouscaud, Fleur ; Cabri, Claudia ; Cagnat, Valérie ; Cantais, Claire ; Choplet, Nadeige ; Christensen, Christina S. ; Corsiglia, Laura ; Costa, Sylvie da ; de Courson, Leïto ; Deltchev, Boris ; Garcia, Ana ; Gilbert, Anne-Sophie ; Gokalp, Sébastien ; Hara, Kôyô ; Herlemont, Vincent ; Jamornmann, Rachanee ; Jordan, Thorsten ; Kim, Hyo Sun ; Kim, Nayoung ; Kister, Thié ; Koo Jeong-a ; Laborde, Pascal ; de Lardemelle, Delphine ; Liniger, Jérôme ; Lin An-Chi ; Maillard, Frédéric ; Majka, Artur ; Neumann, Laure ; Nugues, François ; Palomar, Sandra ; Park, Hyun Jeong ; Pavlin, Monique ; Paz, Alicia ; Polidoro, Julie ; Pomero, Joan ; Raus, Urmo ; Ruel, Jean-Pierre ; Saade, Amal ; Sacriste, Anne-Laure ; Sandillon, Eric ; Stocker, Babette ; Stoianova, Livia ; Termacic, Katarina ; Tschopp, Nicolas ; Valabrègue, Sandra ; Virserius, Regina ; Weltzin, Kirsten ; Wu, Hsiu-Li
biografie
Diplômes 96, Ecole Nationale Supérieure des Beaux-Arts, Paris, 14 février au 6 avril 1997
Frans
boek